COMBINING ABILITY STUDIES FOR YIELD, EARLINESS AND DROUGHT PARAMETERS OF RABI SORGHUM (SORGHUM BIOCOLOR (L.) MONECH) PARENTAL LINES AND HYBRIDS - A. W. MORE,; H. V. KALPANDE,; H. V. PATIL,; D. G. INGOLE,; A. V. NIRDE, (The Bioscan, 2015)
The experiment was confined to fifteen rabi sorghum hybrids (Sorghum bicolor (L.) Moench), developed by crossing three females lines (M-35-1, Phule Anuradha, Parbhani Moti) and five testers (10538, 4189, 10515, 10704, 10593). These hybrids along with check (SPV 1595) and parents were evaluated to study combining ability for 12 yield attributing characters during rabi 2013-14 at Sorghum Research Station, VNMKV, Parbhani. The results revealed, presence of significant differences due to parents, crosses, parents vs crosses and line x tester for almost all the traits. The ratio of á 2 gca: á 2sca variance for general and specific combining ability was less than unity for all the characters. The female line Phule Anuradha and tester, 10593 and 10515 were best general combiners for grain yield and fodder yield. For early maturity and drought parameters, line M-35-1 and Phule Anuradha showed significant gca effects in desirable direction. Significant sca effects were observed in crosses Phule Anuradha X 10515 and Parbhani Moti X 10704 (7.85 and 6.66) for grain yield/plant and Phule Anuradha x 10704 (20.06) for fodder yield/plant. Two crosses, M-35-1 X 10515 and Parbhani Moti X4189, exhibited significant SCA effects in desirable direction for days to 50% flowering. Hence it can be conclude that the parental lines Phule Anuradha, M-35-1 and testers; 10515 and 10593 has scope for breeding high yielding genotypes with early maturity duration adaptable to dry land farming.